Utilization of dietary glucose in the metabolic syndrome - Alemany Marià (Nutrition & Metabolism, 2011)
Abstract This review is focused on the fate of dietary glucose under conditions of chronically high energy (largely fat) intake, evolving into the metabolic syndrome. We are adapted to carbohydrate-rich diets similar to those of our ancestors. Glucose is the main energy staple, but fats are our main energy reserves. Starvation drastically reduces glucose availability, forcing the body to shift to fatty acids as main energy substrate, sparing glucose and amino acids. We are not prepared for excess dietary energy, our main defenses being decreased food intake and increased energy expenditure, largely enhanced metabolic activity and thermogenesis. High lipid availability is a powerful factor decreasing glucose and amino acid oxidation. Present-day diets are often hyperenergetic, high on lipids, with abundant protein and limited amounts of starchy carbohydrates. Dietary lipids favor their metabolic processing, saving glucose, which additionally spares amino acids. The glucose excess elicits hyperinsulinemia, which may derive, in the end, into insulin resistance. The available systems of energy disposal could not cope with the excess of substrates, since they are geared for saving not for spendthrift, which results in an unbearable overload of the storage mechanisms. Adipose tissue is the last energy sink, it has to store the energy that cannot be used otherwise. However, adipose tissue growth also has limits, and the excess of energy induces inflammation, helped by the ineffective intervention of the immune system. However, even under this acute situation, the excess of glucose remains, favoring its final conversion to fat. The sum of inflammatory signals and deranged substrate handling induce most of the metabolic syndrome traits: insulin resistance, obesity, diabetes, liver steatosis, hyperlipidemia and their compounded combined effects. Thus, a maintained excess of energy in the diet may result in difficulties in the disposal of glucose, eliciting inflammation and the development of the metabolic syndrome